Synthesis of Fennel Extract-Based Nanoparticles (AgNPs) Using Proteomics as Larvicide for Aedes Aegypti Mosquitoes - Rafa Athalia Maritza; Isnaini Nursalsabila Gozali (CV. CENDIKIA JENIUS INDONESIA, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia due to the high population of Aedes aegypti mosquitoes. Chemical-based larval control poses risks of resistance development and environmental impacts; therefore, effective and environmentally friendly natural larvicides are urgently needed. This study aimed to analyze the potential of silver nanoparticles (AgNPs) synthesized using essential oil extract of adas pagar (Eupatorium capillifolium) as a larvicide against Aedes aegypti through a proteomic approach. This research employed a laboratory experimental design using third-instar Aedes aegypti larvae as samples. Data were obtained through GC-MS, FTIR, PSA, larvicidal assays, BSLT toxicity tests, in silico analysis, and proteomic analysis, conducted from May to October 2025. Data analysis was performed using logarithmic regression to determine LC₅₀ values and one-way ANOVA. The results demonstrated that adas pagar essential oil-based AgNPs exhibited high larvicidal activity with an LC₅₀ value of 0.08091 µg/mL and caused significant disruption to metabolic and cellular defense proteins in larvae. In conclusion, adas pagar-based AgNPs have strong potential to be developed as an effective natural larvicide, with further in vivo studies and applicative formulation development recommended.